STUDI TENTANG BENTUK DAN MAKNA MOTIF, SERTA FUNGSI PRODUK TENUN NAGARI AMPALU KECAMATAN LAREH SAGO HALABAN KABUPATEN LIMA PULUH KOTA - YOULANDR, Drs. Erwin, M.Sn, Dra. Jupriani, M.Sn (Universitas Negeri Padang, 2015)
This research is purposed to describe the form and meaning of motive, and also function of woven cloth from Ampalu Lareh Sago Halaban. Research method that used here was qualitative research with descriptive approach. Research finding shows that the form and meaning of motive of woven cloth from Ampalu Lareh Sago Halaban come from natural objects, and the meaning is taken from Minangkabau philosophy that is “Alam Takambang Jadi Guru/Learning from Nature”. The form of woven cloth motive from Ampalu Lareh Sago Halaban was based on 8 floral motives, 2 fauna motives, and 5 geometric motives. Functions of woven cloth in Nagari Ampalu Lareh Sago Halaban were clothing and cultural functions.Keywords: form, meaning, and functions of woven cloth of Nagari Ampalu Lareh Sago Halaban